PERAN NINIK MAMAK DALAM PELAKSANAAN PERKAWINAN DI NAGARI SIMPANG LAMA INDERAPURA KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - Fani Yolandri; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In managing the administration of marriage, in addition to the conditionsstipulated in the Marriage Law in Nagari Simpang Lama Inderapura, theprospective bride and groom who are about to marry must be granted the writtenapproval for marry from the Ninik Mamak. This requirement is based on theadditional rules of Nagari Simpang Lama Inderapura which require writtenapproval from the Ninik Mamak for the marriage of his nephew's child that tookplace before they register their marriage to the authorized Office of ReligiousAffairs. Without the written approval from the ninik mamak, the Walinagari officeas the party to create the marriage recommendation letter for the KUA will notfurther process the administration of the marriage file before the marriage permitis completed from the ninik mamak.The purpose of this study was to find out the implementation of marriagein Nagari Simpang Lama Inderapura and to find out the role of ninik mamak inmarriages in Nagari Simpang Lama Inderapura. The type of research for thisthesis is sociological legal research, namely research conducted directly onlocation or in the field to obtain data to provide an overview completely andclearly about the problem under study. The location of this research wasconducted in Nagari Simpang Lama Inderapura. Data collection techniques inthis study were interviews and literature review. The collected data is thenanalyzed qualitatively using the deductive method, namely drawing conclusionsfrom things that are general in nature to be specific.From the results of the research conducted, it can be concluded thatfirst.in the marriage administration needs, aside of the conditions stipulated in theMarriage Law, every niece's who is about to marry in Nagari Simpang LamaInderapura need to seeking for a written marriage approval from the ninikmamak. In practice, without a marriage license from the ninik mamak, the KUAwill refuse to carry out the marriage because this marriage license is as importantas other marriage conditions. Second,the role of the ninik mamak in marriage aasa tribal or clan leader cannot be ignoret. Because in marriage will not take placewithout the knowledge and permission of the ninik mamak.Keywords: Marriage - Ninik Mamak - Administrative Requiremen